Health profile of pregnant women attending urban health centre in Hyderabad, Telangana, India - Ahmad, Sultan Rizwan; Shaik, Mehaboobi; Chandrasekhar, A. (International Journal Of Community Medicine And Public Health, 2016)
Background: Maternal and child mortality is the outcome of multiple factors. Current maternal mortality in India is 254 per 100,000 live births. Improving the maternal and child health is an important public health goal of government of India. To prevent unwanted outcome of pregnancy, antenatal care (ANC) is most important method for early detection and prompt treatment of complications. Methods: A cross sectional study was conducted among pregnant women attending ANC clinic at urban health centre during September 2015 to November 2015. A pre tested semi-structured questionnaire was used for data collection. Data was collected from 102 pregnant women attained ANC clinic during study period. The data was compiled and analyzed using appropriate statistical tools. Results: In present study majority (46%) of pregnant ladies belong to 20-25 years of age group and 26% had consanguinous marriage. In our study gravida 3, gravida 4 and gravid 5 were 29%, 12% and 5% respectively. 52 % of pregnant ladies had 3 ANC visit, almost 62% of pregnant ladies had done haemoglobin examination and 57% blood grouping testing. Pregnancy outcome were live birth in 82.66 % and abortion in 16.69%. 41% were previous LSCS and 9% were home delivery. In this study we found that high risk pregnancy were 59.8% and main reason of being high risk were previous LSCS (52%), anaemia (40%). Conclusions: High quality antenatal care as well as knowledge and practice of community regarding maternal care during pregnancy are important to unwanted outcome of pregnancy.